Driver behaviour during traffic signal change interval - Koh, Puay Ping (2008)
Road junctions are places where conflicting traffic movements meet and hence are critical locations for the overall safety performance of the road network. In Singapore, about one-third of accidents occurred at the road junctions, of which around half occurred at signalised junctions. Many of the accidents can be traced to the period of signal change (intergreen) interval.